Designed to Meet the Requirements of Psycholinguistic - Bayyin, Muhammad Alhaq; Salsabila, Citra Umi Kultsum; Fitriana, Hilma; Amalina, Aida Nur; Al-Zahwa, Defarra; Novanti, Febi Frisca; Nabila, Nazwa Yuki; Padila, Muhammad Ihsan; Apriani, Nurul; Soliha, Naila Bilqis (PT. Ghani Press Group, 2026)
Psycholinguistics is the scientific study of how language is connected to the human mind. It explains how people acquire, understand, produce, and process language by integrating concepts from linguistics, psychology, cognitive science, and neuroscience. One of the main topics is word processing, which discusses how words are stored in the mental lexicon, a mental dictionary containing information about spelling, pronunciation, meaning, and grammatical functions. Word meaning is organized through semantic relationships such as synonyms, antonyms, hyponyms, and hypernyms. Several theories explain lexical representation, including the Hyperspace Analogy to Language (HAL), which measures word relationships based on co-occurrence, and Latent Semantic Analysis (LSA), which analyzes hidden semantic relationships among words. Theories such as the Symbol Grounding Problem and Embodied Semantics emphasize that word meanings are not only represented symbolically but are also grounded in real-world experiences and sensorimotor activities. QRCBN: 62-8550-6283-557